Effect of Debt Default, Disclosure, and Financial Distress on the Receiving of Going Concern Audit Opinions - Ari Tihar; Indriani Puspita Sari; Bambang Leo Handoko (The Winners, 2021)
The research aimed to investigate the impact of debt default, disclosure, and financial distress on the acknowledgment of going concern audit opinion in manufacturing companies. The research applied a quantitative type of data complimented with secondary data retrieved from the official website of Indonesia Stock Exchange. Data obtained from purposive sampling method with 108 samples, consisting of 36 manufacturing companies listed on the Indonesia Stock Exchange in 2016-2018. The research used a logistic regression as data analysis method with several statistical tests which included descriptive statistics, multicolinearity, fit test goodness, etc. The results show that only financial distress influences the acknowledgment of going concern audit opinion, while other independent variables such as debt default and disclosure do not affect the acceptance of going concern audit opinion. The research is limited since it only refers to the manufacturing industry sector. Therefore, it is suggested that future research expand the scope by obtaining more firms’ sample from industrial sectors and using other independent variables to achieve a more accurate results.